Community Participation In The Implementation Of BUMdes Subur Makmur: Partisipasi Masyarakat Dalam Pelaksanaan BUMdes Subur Makmur - Kuria, Mufidatul; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to describe and analyze community participation in the implementation of BUMDes Subur Makmur in Kedungboto Village, Porong District, Sidoarjo Regency. and to analyze and describe the inhibiting and supporting factors for the implementation of BUMDes Subur Makmur in Kedungboto Village, Porong District, Sidoarjo Regency. The research method uses descriptive qualitative research. Data collection techniques obtained are interviews, observation and documentation with one key informant and six informants. Data analysis techniques in data collection, data reduction, data presentation and drawing conclusions. The result of the study indicate that community participation in the implementation of BUMDes Subur Makmur in Kedungboto Village, the dimension of decision making is that the community participates in the from of providing suggestions and input about the BUMDes program during deliberation to determine the type of BUMDes,and communiy parisipation in iimlemrntation is the biggest part of the BUMDes program that has been doe well.but the negative side was the emergence of a pandemiic outbbreak I early 2020 which caused the program to be forced to stop because people had floked to stay away from crowds.